Modeling of Three-Stage High Pressure Heater with Heat Mass Balance in Business Steam Power Plant - A Haqqo; E Tridianto; HE Gayuh Prasetya (UPT Penerbitan Universitas Jember, 2021)
The steam power plant is one of the business selling electrical products to be sold in state electricity distributors. Steam power plant requires a steam generator support system in order to have high efficiency. One of the components for increase efficiency is the High-Pressure Heater (HPH). Generally, The HPH consists of two main parts the shell side where hot steam flows and the tube side where the feedwater flows. So it is necessary to ensure that the energy used can be absorbed maximally in the HPH. To determine the effectiveness of this can be done by modeling according to the installed plant. In this paper, a three-stage HPH model is simulated to determine the performance, and then the Heat Mass Balance calculation will be carried out from the steam used on the shell side and the heated feedwater on the tube side. From the HPH modeling, the simulation will show how much energy can be absorbed by the feedwater. The heat loss at these 3-Stages HPH is 7613.70 kJ/s until 16331.43 kJ/s. Heat loss value is used for performance evaluation. From this modeling of HPH, Simulation shows good results, but the heat loss indicates that the system can be improved. Keywords: High Pressure Heater, Heat Mass Balance. Energy, Heat Loss.